Exploring parents' participation in school governance with the purpose of developing parents' leadership: a formative intervention in a Namibian combined rural school - Nghiteeka, Hileni (Rhodes University, Faculty of Education, Department of Education, 2020)
In a post-independent Namibia, the Education Act 16 of 2001 accorded democratic rights and equal opportunities to all education stakeholders, including parents, to be involved in educational decision-making in schools. This involvement advocated increasing the voice of the educational stakeholders at a grass roots level in an attempt to redress the past injustices of the apartheid education system. However, the studies carried out internationally, as well as in Africa and Namibia, reveal that the issue of democratic participation in school decisions is a restricted reality. This study was conducted in Happy (pseudonym) combined school, a state rural school in the Oshikoto Region, Northern Namibia, aimed at exploring parents' participation in school governance. The study adopted an interventionist approach to develop parents' leadership in school. Framed by a distributed leadership perspective, the main purpose of the study was to seek parents' voices through participation for them to be catalysts for change in transforming parents' leadership in school. For its theoretical and analytical framing, the study adopted the Cultural Historical Activity Theory (CHAT). The study findings revealed that parents' leadership as a concept was understood differently in the case study school and it was practiced within the boundaries of policies. Through the lens of distributed leadership, it was evident that distributed leadership was still in its infancy in the school, as only the characterisations of an authorised distributed leadership were evident in this school. The CHAT analysis revealed that parents' leadership was constrained due to a number of challenges, including language barriers, transport to and from meetings and a lack of support from other parents and some teachers. Study participants, through participation in a Change Laboratory workshop process, envisioned some models such as raising funds to serve as an incentive for parents' School Board members and for an information dissemination committee within the community to do educational campaigns in an effort to enhance parents' leadership in school. To unleash distributed leadership in schools, the study offered some recommendations, including that parents' leadership should be included as part of the curriculum at higher institutions in order to sensitise educators to this critical aspect of leadership, prior to joining the profession. Another recommendation was for stakeholders to make use of the study's findings, when designing workshop materials and conducting workshops. Finally, the study recommended further interventionist research to be conducted on the same research topic, preferably on a larger scale, in an effort to add to the body of knowledge in the field of leadership and management, particularly with regards to parental leadership.
Keywords: Educational leadership -- Namibia; Education, Secondary -- Parent participation --- Namibia; Democracy and education -- Namibia; Transformational leadership -- Namibia; Rural schools -- Namibia; School management and organization --- Namibia; Cultural Historical Activity Theory